(untitled) (Asian Journal of Medical and Biological Research, 2016)
The study was performed to find out the existing status of livestock and poultry in the Saint Martins island, to determine the prevalence of parasitic and other infectious and non-infectious diseases of these, and to find out the existence of intermediate hosts of various parasites in the island. Prevalence of endoparasites in cattle, buffalo and goat was higher in winter than that of summer. Prevalence of stomach worm was highest in goat in both winter (50%) and summer (40%). 31.47% cattle harbored stomach worm infection in winter and 15.79% in summer. More than 20% buffaloes suffered from either single infection with Fasciola and Paramphistomum or in combination in both the seasons. Goat suffered from some extra species like Moniezia and Trichuris and the prevalence is just double in winter than that of summer. Morbidity rate of FMD in cattle is high, although mortality is low. But, in case of chicken, both morbidity and mortality rates were high enough to make a massive loss with respect to number and production due to Ranikhet/Newcastle Disease (ND), pox in the island. About 92.11% of total chicken population was lost every year due to outbreak of ND. Incidence of infectious disease in livestock and poultry in the island is very high as because the farmers cannot immunize the animals through routine vaccination. Even some farmers do not know about the immunization of livestock and poultry, and the veterinary service is not available in the island. Asian J. Med. Biol. Res. December 2015, 1(3): 622-627